EPDSAp: Aplikasi Skrining Baby Blues Berbasis Android dengan Uji Sensitivitas dan Spesifisitas - Novinaldi Novinaldi; Feiby Edwardi; Imam Gunawan; Desi Sarli (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Baby Blues Syndrome is depression that occurs in mothers within a few hours after giving birth, until a few days after delivery, and then it will disappear by itself if given good psychological care. One method to detect postpartum Baby Blues Syndrome is to use the EPDS (Edinburgh postnatal depression scale). However, currently, EPDS can only be done by health workers. Mothers cannot carry out their screening using this method. The purpose of this research is to produce an Android-based EPDS application that will be able to detect the symptoms of baby blues syndrome early after childbirth. Where the detection of the symptoms of baby blues syndrome can be carried out by postpartum mothers themselves quickly and easily, which in turn will reduce the negative impact of this syndrome. This study uses the System Development Life Cycle (SDLC) research method, where the stages of the activity plan are System / Information Engineering and Modeling, Software Requirements Analysis, Systems Analysis and Design, Code Generation, Testing, Implementation, and Maintenance. This EPDS application was built using Android Studio programming which can detect a postpartum mother experiencing the baby blues. This android-based EPDS design has a home screen form design, a questionnaire form design, and a result form design. This application displays results based on a score above 10, so the mother experiences depression or baby blues, while the score between 5 and 9 requires supervision of the mother and re-evaluation using the EPDS application.